2016
DOI: 10.3748/wjg.v22.i42.9324
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of endoscopic assessment of inflammation in ulcerative colitis: Can endoscopic evaluation predict outcomes?

Abstract: Ulcerative colitis (UC) is a chronic inflammatory bowel condition characterised by a relapsing and remitting course. Symptom control has been the traditional mainstay of medical treatment. It is well known that histological inflammatory activity persists despite adequate symptom control and absence of endoscopic inflammation. Current evidence suggests that presence of histological inflammation poses a greater risk of disease relapse and subsequent colorectal cancer risk. New endoscopic technologies hold promis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
0
12
0
5
Order By: Relevance
“…[ 16 , 17 ] Inflammatory markers were not increased in our study cohort as reported in prior studies, which showed that inflammatory markers were not correlated with macroscopic findings and could not contribute to prediction of the disease relapse in UC. [ 18 ] Based on these reasons, we depended on endoscopic assessment for the disease severity. The discrepancy, however, might be attributed to sample size, bias in case enrolment and difference in the evaluation system.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 , 17 ] Inflammatory markers were not increased in our study cohort as reported in prior studies, which showed that inflammatory markers were not correlated with macroscopic findings and could not contribute to prediction of the disease relapse in UC. [ 18 ] Based on these reasons, we depended on endoscopic assessment for the disease severity. The discrepancy, however, might be attributed to sample size, bias in case enrolment and difference in the evaluation system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of endocytoscopic NBI does have some limitations since only a small number of patients with UC can be evaluated using that procedure. The improved mucosal contrast provided by NBI colonoscopies have been successfully used to visualize angiogenesis and thereby detect areas of inflammation in UC more effectively when compared with standard WLE [17].…”
Section: Discussionmentioning
confidence: 99%
“…Grading of inflammatory disease activity is important as well since this too has a prognostic significance and therapeutic implications 14 34 35 36 . Consequently, SBC-CE may become a useful tool for UC management.…”
Section: Discussionmentioning
confidence: 99%